Research on the reuse path of the Third Front construction stock space in China based on value assessment - Liquan Xu; Zhentian Zhang; Gangyi Tan; Lei Yuan (Frontiers of Architectural Research)
The Third Front construction played a crucial role in China's socialist development, resulting in an excess of stock space after four decades of evolution. This study focuses on 113 Third Front plants and mines in western Hubei to explore their contemporary reuse potential. Through field research and statistical analysis, the study examines the layout and conditions of these sites, utilizing the concept of “smart shrinkage” to assess their reuse value. Tools like the minimum cumulative resistance (MCR) model, network analysis, and cluster analysis are employed to develop a reuse value assessment model. The study finds that The Third Front construction plants and mines were concentrated in the transition zone from the plains to the mountains, and idleness and inefficiency became a common problem. These sites exhibit a unique “non-urban, non-rural” layout and possess heritage, asset, and ecological values. The study identifies various reuse strategies, including heritage preservation, property rights transformation, and ecological restoration through rewilding. These measures aim to revitalize the Third Front construction plants and mines, offering theoretical and methodological support for their sustainable development and potential recognition as world cultural heritage.